ASUPAN GIZI, AKTIVITAS FISIK, PENGETAHUAN GIZI, STATUS GIZI DAN KEBUGARAN JASMANI GURU OLAHRAGA SEKOLAH DASAR [Nutritient Intake, Physical Activity, Nutrition Knowledge, Nutritional Status, and Physical Fitness of Elementary School Sport Teacher] - Andini Retno Yunitasari; Tiurma Sinaga; Reisi Nurdiani (Media Gizi Indonesia, 2019)
Sport teacher are central fi gure for attitude, behaviour, and healthy lifestyle change of student, especially at primary school level. This research aimed to analyze nutrition intake, physical activity, nutrition knowledge, nutritional status, and physical fi tness of sport teacher in Jagakarsa subdistrict ptimary school, South Jakarta. Design of this study was cross sectional, with total subject are 53 subjects. Collected data were characteristics of subjects, weight and height, nutritional knowledge, food consumption, physical activity, and physical fi tness (YMCA step test). Data were collected using direct interview, questionnaires, anthropometric measurements, and body fi tness measurement throught YMCA test. Result showed that most of sport teacher in Jagakarsa subdistrict have obesity nutritional status (41.5%), high percentage of body fat (64.1%), light physical activity (45.3%), suffi cient physical fi tness level (47.2%), and nutrition knowledge level was moderate (52%). Energy adequacy level (43.4%) and protein adequacy level (26.4%) of subject classifi ed into severe defi cits, while fat adequacy levels (39.6%) and carbohydrate adequacy levels (73.6%) classifi ed into defi cits. Spearman correlation test showed signifi cant correlation (p<0.05) between carbohydrate intake and body mass index, also signifi cant correlation (p<0.05) between body fat percentage and fi tness level based on pulse rate. Sport teacher need to care about nutritional status, food intake, and physical activity referring to balanced nutrition guidelines in order to prevent increasing obesity problem.